Fusion and fission of molecular assemblies of amphiphilic polypeptides generating small vesicles from nanotubes. Issue 2 (March 2017) - Watabe, Naoki; Joo Kim, Cheol; Kimura, Shunsaku
Abstract: Three amphiphilic block polypeptides, (sarcosine)m ‐ b ‐(l ‐ ord ‐Leu‐Aib)n (L16, D16, D14 ), having different helical chain lengths or helicity are synthesized. A mixture ofL16, D16, andD14 generates vesicles of diameters more than ca. 130 nm by injecting the ethanol solution into water and heating at 90°C for 1 h. On the other hand, when nanotubes composed ofL16 andD14 having ca. 50 nm diameter are mixed with nanosheets composed ofD16, smaller and homogeneous vesicles of ca. 60 nm diameter are obtained with the heat treatment. The time lapse TEM image analysis of the mixtures revealed some transient structures of nanotubes sticking a nanosheet or a vesicle at the open end of nanotubes. The precise size control of vesicles is therefore attainable by using nanotubes as a structural template regulating the size of vesicles near to the nanotube diameter upon the membrane fission processes.